Penyelesaian Sengketa Antara Konsumen dan Pelaku Usaha Menurut Peraturan Perundang-Undangan - Tami Rusli (Universitas Bandar Lampung (UBL), 2012)
Elementary concept is form of consumerism code intrinsically because rule of law protecting importance of consumer in Indonesia not yet is adequate. Although in fact this code have given equivalence domicile between perpetrator and consumer of effort, but in course of its implementation in the reality still there are limitation of ability of his law in finishing dispute that happened between perpetrator and consumer of[is effort, especially when entry of role of jurisdiction institute in checking case of objection of Body decision of[is Solving Of Dispute Consumer. Despitefully several things arranging about how to the solving of consumer dispute also still there are oposition as arrangement of Section 54 Sentence 3 with Section 56 Sentence 2, thereby rule of the sections efficient becoming not